Technical Efficiency in Potato Cultivation in Brahmaputra Valley of Assam, India: Technical efficiency in potato cultivation (SAARC Journal of Agriculture, 2022)
Potato is abundantly grown in Assam and is an important source of income and employment in rural areas of the state. But the productivity of potato in the state is low as compared to other states. Among the various factors, productivity of a crop is significantly influenced by technical efficiency. This paper examines productivity and technical efficiency in potato cultivation in Brahmaputra Valley of Assam, India. The study is based on both secondary and primary data. Primary data were collected from a sample of 400 potato growers. The study applied stochastic frontier production function to estimate technical efficiency and employed logistic transformation model of regression analysis to examine the determinants of technical efficiency. The results showed that potato productivity was positively and significantly affected by seed, fertilizer and manure costs. The mean level of technical efficiency among the farmers was 78%. Technical efficiency was found to be the highest in semi-medium and large land holdings. Technical efficiency was positively affected by land size and negatively affected by capital-labour ratio. The study implies that there is a need to promote use of quality seeds and plant nutrients to improve productivity and encourage extensive farming and use of labour to enhance technical efficiency in potato cultivation.SAARC J. Agric., 20(1): 197-208 (2022)